Effective Tax Rate as a Reflection of Tax Management: An Analysis of Asset Characteristics and the Moderating Role of Institutional Ownership - Yura Karlinda; Luh Pande Eka Setiawati; I Dewa Ayu Oktaviani Putri; Ni Made Yasmini; Ni Made Swinta Setiani (AIBPM Publisher, 2025)
Tax management is defined as a company's effort to minimize tax burdens legally and efficiently. This study aims to examine the effect of fixed asset intensity and inventory intensity on tax management using the Effective Tax Rate (ETR) as a proxy, as well as to assess the moderating role of institutional ownership. The research focuses on textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample was selected using purposive sampling based on specific criteria, resulting in 85 observations. A quantitative approach was employed in this study, using moderated regression analysis. The results show that fixed asset intensity has a significant negative effect on ETR, indicating that companies use depreciation as a legitimate tax management strategy. In contrast, inventory intensity has no significant effect on ETR. Institutional ownership is found to weaken the negative relationship between fixed asset intensity and ETR but does not moderate the relationship between inventory intensity and ETR. These findings contribute to the development of tax accounting literature and offer practical implications for companies and investors in designing effective and regulation-compliant tax management strategies